PERLINDUNGAN HAK CIPTA ATAS MOTIF KAIN KHAS KABUPATEN KUBU RAYA, KALIMANTAN BARAT - Karlina, Dina (TANJUNGPURA LAW JOURNAL, 2021)
Abstract The unique motif which is one of the cultural identities of the archipelago needs to be registered as intellectual property rights that have moral and economic values. Cultural diversity in West Kalimantan has resulted in various forms of work in the form of the unique motif in their respective regions. Researchers study the copyright issue of the the unique motif of the Kubu Raya Regency. Researchers used normative legal research, namely analyzing articles in statutory regulations and their implications for research subjects. The unique motif of Kubu Raya Regency (Sail Meretas, Gelombang Muare, Kelambu Raje, Harmoni Serampai and Gelombang Muare Reborn) are among the objects that can be protected under the Copyright Law, based on Article 40 letter j, which includes other motif artworks. The field study was carried out by identifying legal protection measures implemented by the local government against the copyright of local special cloth motifs. Both data were analyzed qualitatively. It was found that efforts to protect the unique motif of Kubu Raya Regency already exist, for example, issuing a Regent Regulation regarding the unique motif of Kubu Raya Regency, registering the unique motif of Kubu Raya Regency at Directorate General of Intellectual Property, promoting and socializing and coordinating The unique motif of Kubu Raya Regency at the National Craft Council of Kubu Raya Regency. Based on the DJKI database, the Gelombang Muare Motif was registered with the copyright to the Director General of Intellectual Property Rights. Local governments need to record all the unique motif of Kubu Raya Regency, including those that have been recorded but modified. The local government needs to develop the economic benefits of the unique motif of Kubu Raya Regency. The concentration of sales coordination for Kubu Raya Regency's unique motif products in Dekranasda must be accompanied by vigorous marketing efforts so that the products can compete in the market. Abstrak Motif kain khas yang merupakan salah satu identitas budaya nusantara perlu didaftarkan sebagai HKI yang bernilai moril dan ekonomis. Keberagaman kebudayaan di Kalimantan Barat menghasilkan berbagai bentuk karya dalam bentuk Motif Kain Khas di wilayahnya masing-masing, Peneliti membangun penelitian yang sesuai dengan kebutuhan kajian Hak Cipta pada setiap motif kain khas di wilayah Kalimantan Barat. Peneliti akan mengkaji permasalahan Hak Cipta terhadap motif kain khas wilayah Kabupaten Kubu Raya. Peneliti menggunakan penelitian hukum normatif yaitu menganalisis pasal-pasal dalam peraturan perundang-undangan dan implikasinya terhadap subjek penelitian. Motif-motif kain khas Kabupaten Kubu Raya (Layar Meretas, Gelombang Muare, Kelambu Raje, Harmoni Serampai dan Gelombang Muare Reborn) termasuk objek yang dapat dilindungi dengan Undang Undang Hak Cipta, berdasarkan Pasal 40 huruf j, yaitu termasuk karya seni motif lain. Studi lapangan dilaksanakan dengan mengidentifikasi upaya perlindungan hukum yang dilaksanakan pemda terhadap hak cipta motif kain khas setempat. Kedua data kemudian dianalisis secara kualitatif. Ditemukan bahwa upaya perlindungan terhadap Motif kain khas Kabupaten Kubu Raya sudah ada misalnya, menerbitkan Peraturan Bupati mengenai motif khas Kabupaten Kubu Raya, melakukan pencatatan motif kain khas Kabupaten Kubu Raya pada DJKI melakukan promosi dan sosialisasi serta koordinasi produk khas motif Kabupaten Kubu Raya di Dekranasda Kabupaten Kubu Raya. Berdasarkan database DJKI, baru Motif Gelombang Muare yang sudah didaftarkan Hak Ciptanya ke Dirjen HAKI. Pemerintah Daerah perlu melakukan pencatatan terhadap semua motif kain khas Kubu Raya, termasuk motif yang telah tercatat namun dimodifikasi. Pemda perlu mengembangkan manfaat ekonomis dari motif kain khas Kubu Raya. Pemusatan koordinasi penjualan produk motif kain khas Kubu Raya di Dekranasda harus dibarengi dengan upaya pemasaran yang gencar agar produk dapat berkompetisi di pasar.